IDENTIFIKASI MODEL PENYULUHAN PARTISIPATIF PADA PETANI PADI DI KABUPATEN ACEH UTARA - Martina, Tina; Zuriani, Zuriani; Riani, Riani; Zahara, Hafni; Barmawi, Barmawi (LPPM Universitas Malikussaleh - Indonesia, 2024)
Aceh Utara has the largest number of farmers in Aceh Province, namely 82,877 farmers who are members of 4,939 farmer groups. This shows that extension activities are carried out well in Aceh Utara. Extension activities are generally carried out starting from planning, implementation and evaluation activities. However, these activities need to be carried out in a participatory manner by actively involving rice farmers in each activity so that an appropriate model in the extension program is important to achieve targeted extension goals. The aim of this research is to identify a participatory extension model for lowland rice farmers, analyzed descriptively qualitatively. The research results showThe participatory extension model in Aceh Utara is implemented according to procedures, but there is a need to improve the model, namely by establishing farmer contacts and activating their involvement as an extension of the extension agent and as someone who is most trusted by farmers so that the extension program can run well and make it possible to minimize the obstacles faced instructor.